2020
DOI: 10.1111/imj.14640
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world direct oral anticoagulant experience in atrial fibrillation: falls risk and low dose anticoagulation are predictive of both bleeding and stroke risk

Abstract: Background: Clinical trials have demonstrated that direct oral anticoagulants (DOAC) are non-inferior to vitamin K antagonist for stroke prevention in non-valvular atrial fibrillation (AF) with comparable safety outcomes; however, real-world Australian data are limited. Aims: To evaluate local real-world DOAC use focussing on safety, particularly in highrisk patients. Methods: A retrospective evaluation of 658 patients commenced or continued on DOAC between September 2013 and September 2016 for non-valvular AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…A recent study found that antiarrhythmic therapy usage increased the risk of fallrelated injury and syncope compared with rate lowering monotherapy, with the highest risk during the first 14 days [38]. Applicable AF patient populations may use anticoagulants to diminish stroke risk, and while serving a protective effect, may be considered as a potential modifier of the severity of injury following falls due to increased bleeding risk [35,[39][40][41][42].…”
Section: Atrial Fibrillation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that antiarrhythmic therapy usage increased the risk of fallrelated injury and syncope compared with rate lowering monotherapy, with the highest risk during the first 14 days [38]. Applicable AF patient populations may use anticoagulants to diminish stroke risk, and while serving a protective effect, may be considered as a potential modifier of the severity of injury following falls due to increased bleeding risk [35,[39][40][41][42].…”
Section: Atrial Fibrillation Therapymentioning
confidence: 99%
“…Several studies have suggested that following trauma, direct oral anticoagulants are associated with less major bleeding events as compared with warfarin [40,[48][49][50] and better outcomes [51], although others have suggested no difference between them [52,53]. Many authors have concluded that while the benefits of anticoagulation most often outweigh the risks [54], a case-by-case basis should be undertaken to properly balance all possible outcomes [41,42,55]. The most recent ESC guidelines state that anticoagulation among patients with AF and fall history should only be withheld from patients with severe uncontrolled falls (e.g., epilepsy or multisystem atrophy), or in situations where compliance and adherence cannot be guaranteed [56].…”
Section: Atrial Fibrillation Therapymentioning
confidence: 99%
“…Scores of ≥3 points are associated with a 3.74% annual risk of bleeding, which is considered a high risk ( 49 ). As a history of bleeding was found to be the greatest risk factor (HR 3.52, 95% CI 1.22-10.17) ( 50 ), caution is required for such cases.…”
Section: Strategies For Administering Anticoagulant Therapy To Frail mentioning
confidence: 99%
“…No consensus has been reached regarding whether or not anticoagulants should be discontinued due to a history of one fall. However, if a fall has resulted in a hemorrhagic complication or has required hospitalization ( 17 , 50 ), withholding anticoagulant therapy is reasonable.…”
Section: Strategies For Administering Anticoagulant Therapy To Frail mentioning
confidence: 99%
See 1 more Smart Citation